The present-day problem of woman's education - Allen, Jessie (My University, 1908)
Introduction: At the present day it is scarcely conceivable that at one time, not long since, women were deemed unworthy subjects for an education. As in China to-day, it was once thought in all other countries that woman did not need an education and that if she did she had not the ability to acquire it.
Citation: Allen, Jessie. The present-day problem of woman's education. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Women; Women's Rights; Education; Graduating theses; Senior theses; Theses